Application of The Importance Performance Analysis Method for The Development Strategy of Savings and Loans Cooperatives in Garut Regency - Murwenie, Ira; Hassanudin, Abdul Fatah (Jurnal Wacana Ekonomi, 2024)
The aim of this research is to determine the map of the development of Savings and Loans Cooperatives (KSP) in Garut Regency using the Importance Performance Analysis method which will then be implemented into a SWOT (Strengths, Weakness, Opportunity, Threats) analysis to determine the appropriate strategies. appropriate to encourage the development of KSP in supporting MSME financing in Garut Regency. This research uses secondary data with a total research sample of 165 KSP units spread across 42 sub-districts. The research results found that the number of KSPs in Garut Regency was only 26.19% of all sub-districts, where KSPs were in Garut Kota, Tarogong Kidul, Tarogong Kaler, Bayongbong, and Banyuresmi Districts; has enormous potential for developing KSP strategies and should be used as a pilot area for KSP development in other sub-districts. Overall, the research results can be recommended for further exploring the performance of KSP in certain sub-districts so that a more implementable KSP development strategy can be determined.